ANALISA DAN PERANCANGAN MECHANICAL BAR SCREEN PADA INSTALASI PENGOLAHAN AIR MINUM (Analysis and Design of Mechanical Bar Screen in Drinking Water Treatment Plants) - Wisnu Wijaya (UNIVERSITAS KEBANGSAAN, 2019)
Abstract: Installation to process raw water into consumable water consists of processing units that have their respective functions. The selection of these units is based on parameters that must be set aside in accordance with the results of water quality checks. The final result of processing must meet the standards set by the government. In addition to technical aspects, which must be considered also in the determination of the unit on the installation of drinking woter is an economic aspect and the availability of human resources.One of the components contained in the installation of drinking water is a mechanical bar screen. Cleaning of garbage on the bar screen is mechanically intended for cleaning to take place effectively and is not limited by time or weather conditions around the drinking water installation. From the design results obtained motor power required 1226.936 watts while the tensile stress of the flexrake results from the design calculation of . in this design also used material stailess stell AISI 304.Keywords: Designing, Mechanical Bar Screen,Abstrak: Instalasi untuk mengolah air baku menjadi air yang dapat dikonsumsi terdiri dari unit-unit pengolahan yang memiliki fungsi masing-masing. Pemilihan unit-unit ini didasarkan pada parameter-parameter yang harus disisihkan sesuai dengan hasil pemeriksaan kualitas air. Hasil akhir dari pengolahan harus memenuhi bakumutu yang ditetapkan oleh pemerintah. Selain dari segi teknis, yang harus diperhatikan juga dalam penentuan unit pada instalasi air minum adalah segi ekonomis dan ketersediaan sumber daya manusia.Salah satu komponen yang terdapat pada instalasi air minum adalah mechanical bar screen. Pembersihan sampah pada bar screen secara mekanik dimaksudkan agar pembersihan dapat berlangsung secara efektif dan tidak dibatasi oleh waktu maupun kondisi cuaca di sekitar instalasi air minum. Dari hasil perancangan didapatkan daya motor yang dibutuhkan 1226.936 watt sedangkan tegangan tarik dari pada flexrake hasil dari perhitungan perancangan sebesar . pada perancangan ini juga digunakan material stailess stell AISI 304.Kata Kunci : Perancangan, Mechanical Bar Screen,